Design of gas-jet drive with vortex valve thrust control system - A. Yu. Uss; A. V. Chernyshev; A. S. Pugachuk (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2021)
The article is devoted to the design of a gas-jet drive with a traction control system using a vortex valve. A diagram is given and the principle of operation of a vortex jet device designed to control the gas flow is considered. The selected scheme of a vortex jet device with a distributed supply of a feed and a concentrated supply of control gas flows, designed to control the thrust of a gas-jet engine. The profiling of the Laval nozzle was carried out using a simplified technique from [G. N. Abramovich, Applied Gas Dynamics]. Computational and theoretical studies of the gas flow from a gas-jet drive with a vortex valve in the maximum thrust mode and in the thrust control mode have been carried out